Perancangan Aplikasi Perekrutan Karyawan Baru Di Pt. Katolec Indonesia Berbasis Web - Maharani Pramesti Apriliyani; Alvino Octaviano (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The employee recruitment process by sending application files via email is considered to be less effective in carrying out the employee recruitment process. PT. Katolec Indonesia is one of the companies in the employee recruitment process that still uses e-mail sent to HRD. This has an impact on incoming messages in large quantities causing spam, takes quite a long time to select application data and the selection of employees does not match the required criteria company.This study aims to create a website-based employee recruitment application to make it easier for companies to recruit and select employees according to the required criteria, in addition to making it easier for job seekers to apply for jobs. In the research using the SDLC (Software Development Life Cycle) system development method waterfall model which includes the stages of system planning, analysis, design, implementation, testing and maintenance. The system is built using the PHP programming language, the database server uses MySQL. The results achieved in this study are web-based employee recruitment applications that are expected to help HRD in the hiring process quickly and according to the criteria the company wants.